Factorization algebras in quantum field theory, Volume 2 - Costello, Kevin 1977-; Gwilliam, Owen (Cambridge University Press, 2021)
Factorization algebras are local-to-global objects that play a role in classical and quantum field theory that is similar to the role of sheaves in geometry: they conveniently organize complicated information. Their local structure encompasses examples like associative and vertex algebras; in these examples, their global structure encompasses Hochschild homology and conformal blocks. In this second volume, the authors show how factorization algebras arise from interacting field theories, both classical and quantum, and how they encode essential information such as operator product expansions, Noether currents, and anomalies. Along with a systematic reworking of the Batalin-Vilkovisky formalism via derived geometry and factorization algebras, this book offers concrete examples from physics, ranging from angular momentum and Virasoro symmetries to a five-dimensional gauge theory
Title from publisher's bibliographic system (viewed on 14 Sep 2021)
From Gaussian measures to factorization algebras -- Prefactorization algebras and basic examples -- Free field theories -- Holomorphic field theories and vertex algebras -- Factorization algebras: definitions and constructions -- Formal aspects of factorization algebras -- Factorization algebras: examples
Keywords: Quantum field theory / Mathematics; Noncommutative algebras; Geometric quantization; Factors (Algebra); Factorization (Mathematics)